Mid-term outcome after arthroscopic treatment of femoroacetabular impingement: development of a predictive score. Issue 3 (May 2019) - Pierannunzii, Luca; Di Benedetto, Paolo; Carulli, Christian; Fiorentino, Gennaro; Munegato, Daniele; Panascì, Manlio; Potestio, Domenico; Randelli, Filippo; Della Rocca, Federico; Rosolen, Valentina; Giangreco, Manuela; Santori, Nicola
Purpose: To build a post-arthroscopy outcome-predictive score (POPS) associated with the likelihood of lasting benefit after arthroscopic treatment of femoroacetabular impingement (FAI) and based solely on unambiguous preoperative information. Methods: A population of 220 FAI patients, operated on with standard techniques by orthopaedic surgeons trained in hip arthroscopy in 6 different centres, was evaluated physically or by telephone interview 2 to 5 years after surgery. The criteria of successful mid-term outcome (SMO) were agreed upon by all authors. A multivariate logistic regression, adjusted for patient's age and centre, was applied to predict SMO. In the model, the variables associated with the outcome were included and the relative ORs (odds ratios) were used to compute the FAI-POPS (FAI - post-arthroscopy outcome-predictive score). A ROC (receiver operating characteristic) curve was plotted and the optimum cut-off was calculated. Results: 155 patients out of 220 showed a successful mid-term outcome. The optimum cut-off of FAI-POPS was calculated to be 6.3 and with this threshold it proved a sensitivity of 0.66 and a specificity of 0.69, a positive predictive value of 0.84 and a negative predictive value of 0.46. Conclusions: The standard arthroscopic treatment of FAI resulted in satisfactory persistent symptom relief for about 70% of patients. No or minimal osteoarthritis, short time elapsed from the appearance of symptoms and high preoperative modified Harris Hip Score are independent predictive factors of SMO. The FAI-POPS is obtained as sum of 3 odds ratios corresponding to the above prognostic factors and is a useful predictor of mid-term outcome after conventional arthroscopic FAI treatment.